Online Marketing and Its Impact on the Profitability of Student-Owned Snack Businesses in Kendari City (A Case Study of KUKITO) - Bulan, Kezia Ada’ Embong; Abdullah, Weka Gusmiarty; Yusria, Wa Ode (International Journal of Technology and Education Research, 2025)
This research is motivated by the evolution and transformation in technology, which has also influenced the economic sector. Online marketing is one form of community adaptation in the era of digital transformation, creating both opportunities and new challenges for business actors in maximizing profits. KUKITO, or Kukis Kabuto, is an innovative product developed by students of Halu Oleo University during their participation in the Student Entrepreneurship Development Program (P2MW) in 2024. Online marketing was applied as one of the strategies to optimize profits, and eventually, KUKITO achieved third runner-up in the food and beverage category (early stage) at the 13th KMI EXPO in 2024. The effectiveness of online marketing in increasing profits remains a subject requiring further analysis, especially in the context of student snack businesses such as KUKITO. The purpose of this study is to describe the application of marketing strategies and analyze the impact of online marketing on KUKITO's profitability. The research location was determined purposively, with the subject being the owner of KUKITO. To describe the marketing application, the researcher used qualitative descriptive analysis tools with variables including marketing strategy and marketing mix. Meanwhile, to analyze the impact of online marketing on KUKITO’s profit, a paired t-test was used to compare two related samples—profits gained from online and offline marketing over 28 weeks (June–December 2024). The research findings show that the implementation of online and offline marketing at KUKITO differed by 60% in terms of the marketing concept variables and 75% in terms of the marketing mix. Overall, there is a significant difference between KUKITO’s online and offline marketing strategies. This is evident in the sales results: offline marketing resulted in 2,208 products sold, averaging 78 products per week, which is higher than online marketing with 1,446 products sold, averaging 51 products per week. However, based on the results of the t-test, the significance value (two-tailed) was 0.249 (> 0.05), so it can be concluded that there is no significant difference between the profits of online marketing and offline marketing in the KUKITO business during the research period